Characterization of the in vitro and in vivo properties of CFZ533, a blocking and non‐depleting anti‐CD40 monoclonal antibody. Issue 12 (24th May 2018) - Ristov, Jacinda; Espie, Pascal; Ulrich, Peter; Sickert, Denise; Flandre, Thierry; Dimitrova, Mirela; Müller‐Ristig, Dorothee; Weider, Doris; Robert, Gautier; Schmutz, Patrick; Greutmann, Barbara; Cordoba‐Castro, Francisco; et al.
Abstract : The CD40‐CD154 costimulatory pathway is essential for T cell–dependent immune responses, development of humoral memory, and antigen presenting cell function. These immune functions have been implicated in the pathology of multiple autoimmune diseases as well as allograft rejection. We have generated CFZ533, a fully human, pathway blocking anti‐CD40 monoclonal antibody that has been modified with a N297A mutation to render it unable to mediate Fcγ‐dependent effector functions. CFZ533 inhibited CD154‐induced activation of human leukocytes in vitro, but failed to induce human leukocyte activation. Additionally, CFZ533 was unable to mediate depletion of human CD40 expressing B cells. In vivo, CFZ533 blocked primary and recall T cell‐dependent antibody responses in nonhuman primates and abrogated germinal formation without depleting peripheral blood B cells. We also established a relationship between plasma concentrations of CFZ533 and CD40 pathway‐relevant pharmacodynamic effects in tissue. Collectively these data support the scientific rationale and posology for clinical utility of this antibody in select autoimmune diseases and solid organ transplantation. Abstract : Using a combination of in vitro and in vivo experiments, this study demonstrates that CFZ533 is a non‐depleting, pathway‐blocking anti‐CD40 monoclonal antibody yielding data that support clinical development in solid organ transplantation and autoimmune disease.